Supervision and Control of Regional Assets at the Regional Asset and Financial Management Agency of City X, East Java: A Perspective of the Characteristics of Good Practice - Hago, Afdholifah Ainunia; Kholmi, Masiyah; Leniwati, Driana (Yayasan Sinergi Kawula Muda, 2025)
Despite having received twelve consecutive unqualified audit opinions (WTP), the supervision and control of regional assets (Barang Milik Daerah/BMD) in City X, East Java, still face significant challenges, including undocumented assets and weak legal safeguards. These issues highlight a persistent gap between formal compliance and effective asset governance, a condition also found in previous studies across Indonesia. Unlike earlier research that primarily focused on regulatory adherence, this study applies the internationally recognized good practice framework to evaluate asset management in a localized Indonesian context. Through a qualitative case study of BPKAD City X, particularly its Subdivision for Supervision and Control, data were collected via semi-structured interviews and document analysis, then analyzed using Miles & Huberman’s interactive model. The findings reveal that while practices such as asset recording, digitization, transparency, and training are being implemented, strategic tools like the Strategic Asset Management Plan (SAMP), Life Cycle Costing (LCC), and multi-year planning remain underutilized. This study not only fills a gap in the literature by introducing a structured, internationally informed framework to the Indonesian local governance context but also contributes to ongoing discussions on public sector reform, offering insights into how institutional capacity and administrative culture influence the implementation of good practices in decentralized asset management.